Brief Exposition of Religious Experience in Semitic Religion - Ahmad Nabil Amir; Tasnim Abdul Rahman (Rabbanica: Journal of Revealed Knowledge)
The paper discusses the religious experience of Semitic faith in Abrahamic tradition. It firstly discusses its underlying approach as enshrined in classical religious thought concerning its meta-religious principle, methodology and traditional framework. In analysing the history and tradition of the Abrahamic Faiths, it tries to encapsulate this within the framework of comparative religion, signifying its historical development and importance in inspiring convivencia in a global context. This was analysed from classical works that study the science of religion or religionswissenschaft and its methodology that brought forth its fundamental approach and principles. The study is based on a qualitative framework using descriptive and analytical methods. It also surveys modern development in this field of study and its position in espousing interfaith dialogue and the mutual heritage of our common humanity that highlighted the spirit of La-Convivencia of such an inclusive and pluralistic force, especially in the Malay Basin. The findings show the unprecedented influence and presence of the Abrahamic seeds in the world’s religion, especially of the Semitic line of origin.